Factors Influencing Information Literacy Collaborative Teaching in Higher Education Institution Libraries in China - Shanfang, Qin; Bunawan, Ap-azli; Abd Aziz, Nor Erlissa (Journal of Ecohumanism, 2025)
With the rapid development of information technology and the in-depth promotion of informatization in higher education, the importance of information literacy education in the libraries of higher education institutions has become increasingly prominent. As an effective way of information literacy education, the cooperative teaching model has gradually attracted extensive attention. However, there are many influencing factors in the process of information literacy cooperative teaching in Chinese higher education institutions. This study aims to explore these influencing factors and systematically analyze the key factors influencing the cooperation between libraries and teachers, faculties and other departments in higher education institutions to carry out information literacy education through literature analysis, including the lack of co-teaching as part of the organization’s strategic goals, the lack of support from authoritative organizations, and the lack of financial support. The results of this study will provide a theoretical basis and practical suggestions for optimizing the cooperative teaching mode of information literacy in libraries of higher education institutions in China, to promote the sustainable development of information literacy education.